Utilising TikTok as a Digital Learning Tool to Improve Vocabulary Mastery - Pritalia Dorasa; Aminah Suriaman; Anjar Kusuma Dewi; Afrillia Anggreni (Journal of General Education and Humanities, 2025)
This study aimed to ascertain whether the use of the TikTok app as a digital learning tool could enhance vocabulary acquisition among grade 11 students at MAN 2 Palu. The study was motivated by the observation that many students demonstrated low vocabulary mastery, with limited lexical resources that hindered their ability to use vocabulary effectively in productive language tasks. The researchers employed a quasi-experimental design, assigning students to two groups: an experimental class that utilised TikTok-based learning and a control class that received conventional instruction. A total of 64 students were selected through random sampling and divided equally into two groups. Both groups were given a pre-test and a post-test to measure vocabulary improvement. The collected data were analysed using descriptive statistics and an independent-samples t-test at a significance level of 0.05. The findings revealed a significant difference between the post-test mean scores of the experimental group (86.13) and the control group (68.84). A paired-samples t-test confirmed that the difference was statistically significant, lending support to the idea. These findings suggest that the TikTok app has a positive impact, enhancing students' vocabulary mastery. Therefore, TikTok can be considered an effective and engaging digital media platform that supports English as a Foreign Language (EFL) learning, particularly in improving students' vocabulary mastery.